Decreased incidence of Kawasaki disease in South Korea during the SARS-CoV-2 pandemic - Oh, Kyung Jin; Lee, Sang-Yun (Frontiers in Pediatrics, 2024)
3% of all patients with KD were infants, a percentage significantly higher than that of the previous year (p <0.001). There was biphasic seasonality in the monthly Kawasaki disease incidence. The Kawasaki disease incidence was the highest in winter followed by that in early summer.After the start of the pandemic, the Kawasaki disease incidence decreased, and the percentage of patients with Kawasaki disease aged <1 year increased. These findings provide support for the hypothesis suggesting an infectious trigger in Kawasaki disease.